2022
DOI: 10.1186/s12880-022-00814-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and feasibility of optic nerve diffusion MRI techniques: single-shot echo-planar imaging (EPI), readout-segmented EPI, and reduced field-of-view diffusion-weighted imaging

Abstract: Background Diffusion-weighted imaging (DWI) is an essential technique for optic nerve diseases. However, the image quality of optic nerve DWI is decreased by the distortions and artifacts associated with conventional techniques. In order to establish this method as a critical tool in optic nerve diseases, reproducibility and feasibility of new technical and conventional approaches of DWI need to be systematically investigated. Methods DWIs were acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Several studies demonstrated that rsEPI provides superior image quality of dMRI measurements in the ON, compared with those acquired using a conventional single-shot EPI. 98 103 The drawback of this method is its prolonged acquisition time, which limits applicability to studies of clinical populations. Simultaneous multi-slice rsEPI 104 has been proposed to mitigate this limitation, and recent work demonstrated that it reduces image distortion of dMRI measurements of the ON and, therefore, reduces the impact of image blurring caused by distortion correction procedures on tractometry results.…”
Section: Tractometry Of Early Visual White Matter Tractsmentioning
confidence: 99%
“…Several studies demonstrated that rsEPI provides superior image quality of dMRI measurements in the ON, compared with those acquired using a conventional single-shot EPI. 98 103 The drawback of this method is its prolonged acquisition time, which limits applicability to studies of clinical populations. Simultaneous multi-slice rsEPI 104 has been proposed to mitigate this limitation, and recent work demonstrated that it reduces image distortion of dMRI measurements of the ON and, therefore, reduces the impact of image blurring caused by distortion correction procedures on tractometry results.…”
Section: Tractometry Of Early Visual White Matter Tractsmentioning
confidence: 99%